2019
DOI: 10.21278/tof.42401
|View full text |Cite
|
Sign up to set email alerts
|

Surface Integrity after Turning a Duplex Stainless Steel with Respect to Tool Geometry

Abstract: This study deals with surface integrity expressed in terms of stress state as well as microstructure alterations after turning a duplex stainless steel. Residual stresses and the presence of strain-induced martensite are studied as functions of the rake angle. Residual stresses of surface and sub-surface layers were determined by the use of the X-ray diffraction and hole-drilling techniques. X-ray diffraction enables us to distinguish between residual stresses in each phase separately, which is not possible wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Increasing the cutting speed during the turning process of duplex stainless steel can reduce the maximum microhardness by 10%. Apek et al 4 , based on dislocation theory, propose that austenite is more prone to work hardening, while ferrite exhibits high strength. By measuring the surface integrity of the cut duplex stainless steel, it was found that due to the different yield ratios of the two-phase, austenite, as a plastic phase, undergoes more dislocation motion during deformation, resulting in higher residual stress.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the cutting speed during the turning process of duplex stainless steel can reduce the maximum microhardness by 10%. Apek et al 4 , based on dislocation theory, propose that austenite is more prone to work hardening, while ferrite exhibits high strength. By measuring the surface integrity of the cut duplex stainless steel, it was found that due to the different yield ratios of the two-phase, austenite, as a plastic phase, undergoes more dislocation motion during deformation, resulting in higher residual stress.…”
Section: Introductionmentioning
confidence: 99%